First Adiabatic Invariants and Phase Space Densities for the Jovian Electron and Proton Radiation Belts—Galileo and GIRE3 Estimates. Issue 1 (20th January 2021) - Garrett, H. B.; Jun, I.
Abstract: The fluxes and phase space densities for a fixed first adiabatic invariant for high‐energy electrons and protons provide important inputs for various scientific studies for determining the physics of particle diffusion and energization. This study provides estimates of the first adiabatic invariant and phase space density based on the complete and large data base available from the Energetic Particle Detector (EPD) on Galileo for the Jovian environment. To be specific, 10 min averages of the high‐energy electron and proton data are used to compute differential flux spectra versus energy between L = 8 and 25 over the mission. These spectra provide estimates of the differential fluxes and phase space density for constant first adiabatic invariants between 10 2 and 10 5 MeV/G. As would be expected, the electron and proton fluxes and phase space densities generally trend lower as the planet is approached. The results indicate that, whereas the overall trends for each orbit are consistent, detailed orbit to orbit variations can be observed. Galileo orbit C22 is presented as an example of deviations from the mean downward trend. To validate the Galileo results and extend the findings into L = 3, the GIRE3 model was also used to compute the fluxes and phase space densities for constant first adiabatic invariant versus L ‐shell. Comparison between GIRE3 and EPD demonstrates that the model adequately reproduces the EPD data trends and they consistently show additional variations near Io. This provides proof that the GIRE3 is a useful starting point for diffusion analyses and similar studies. Plain Language Summary: Long‐term high‐energy radiation environment at Jupiter is studied in this study by using an extensive data set collected by the Galileo Energetic Particle Detector (EPD). This is the first time that the EPD high‐energy data are used in its entirety for this purpose. The results from the long‐term (∼7 years) observation confirm that trapped protons and electrons are indeed diffusing inward to the planet although there are some short‐term orbit‐to‐orbit variations. This finding is shown to be consistent with the GIRE3 model output which has been and is being used for various Jovian mission designs (e.g., Juno, Europa Clipper, Europa Lander Concept Study). Key Points: The long‐term dynamics of particle trapping in the Jovian magnetosphere is investigated using high‐energy electron and proton data First adiabatic invariant and phase space densities are computed using the Energetic Particle Detector data as well as using the GIRE3 model Both electrons and protons show a clear downward trend in flux and phase space density at constant first adiabatic invariant as the planet is approached